Kynurenic acid and positive symptoms in schizophrenia - Karakuła, Hanna; Flis, Marta; Szymona, Kinga; Studenna, Magdalena (Current Problems of Psychiatry, 2012)
Kynurenic acid (KYNA) is a neuroactive metabolite of tryptophan that is synthesized in the brain mainly by astrocytes. Growing evidence indicates an anticonvulsant and neuroprotective role of KYNA. Differences in kynurenic acid concentration are described in the course of diseases such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, epilepsy, depression, anxiety disorder or schizophrenia. Progress in the field of schizophrenia research points out that dopamine plays only an intermediary role in the pathogenesis of the disease and that there is a necessity forfinding a source of this disorders in relation to other neurotransmitters, in particular as far as the glutamatergic system is concerned. In reference to searching for the pathogenesis of positive symptoms in schizophrenia, it is vital to find an element linking dopaminergic hyperactivity with glutamatergichypoactivity. KYNA is a nonselective antagonist of ionotropic receptors for excitatory aminoacids: NMDA receptor, kainic acid receptor, AMPA receptor. Moreover, KYNA is an antagonist of an independent of strychnine glicyne site of the NMDA receptor complex. Recent research indicates that cerebrospinal fluid level of KYNA is elevated in schizophrenic patients. Pharmacologically elevated level of KYNA leads to increased dopaminergic activity of the neurons in the rat ventral tegmental area. Research provides evidence that KYNA has inhibiting influence on glutamate release. Elevated level of KYNA causes an effect similar to the effect demonstrated after administration of ketamine or phencyclidine and is associated with psychomimetic effects. To sum up, the raised dopaminergic activity in the mesolimbic system and glutamatergic hypoactivity play an important role in pathogenesis of positive symptoms in schizophrenia and KYNA is a modulator of both of these mechanisms.